Portable Walk-in Closet Pada Interior Small Living Space - Mega Jaya Sari Je; Adi Santosa; filipus priyo suprobo (Intra, 2014)
Walk-in closet is a closet large enough to walk inside to store clothes or other fashion objects. All fashion needs can be stored and attractively furnished in it. However, a walk-in closet requires a fairly wide area, while the living space now days is becoming increasingly limited. Thus, a it is in general can only be enjoyed by people with large enough living space. Therefore, it needs a storage that can effectively meet the growing needs of users. With the field survey and study of the literature on the design of a walk-in closet, the design of portable walk-in closet intended to meet the needs of fashion storage media to be more effective by most people, especially people who haves limited living space.